Village Governance in Transition: Collaborative Networks, Spatial Strategy, and Sustainable Development - Ali Darlis, Muh Akbar; Muhammad Ikbal; Akhwan Ali (Universitas Muhammadiyah Makassar, 2025)
This research focuses on the dynamics of village governance and development by highlighting the urgency of transformation towards an inclusive, transparent, collaborative, and adaptive governance model to global change. The background of this research is based on the fact that villages in developing countries face serious challenges, ranging from development gaps, the impacts of climate change, to the need for digitalization of governance. To address these challenges, this research uses a bibliometric approach with the Scopus database and the support of R-Studio Biblioshiny, VOSviewer, and CiteSpace analysis tools, which enable mapping of research trends, academic collaboration networks, thematic evolution, and the direction of development of village governance theory and practice. The main findings indicate that digital governance, including the implementation of e- Government and open data programs, has significant potential to increase transparency, accountability, and citizen participation, although it still faces obstacles such as inconsistent data quality, resistance to boundaries, and limited digital literacy. Furthermore, governance based on participation and collaboration between stakeholders has been shown to strengthen social cohesion, optimize the use of social capital, and increase the effectiveness of local development. Furthermore, the integration of spatial governance and socio-ecological resilience approaches plays a crucial role in strengthening rural adaptation to climate change and urbanization, while the development of rural tourism and agrotourism opens up strategic opportunities for transforming local resources into sustainable economic value. The significance of this research lies in the novelty of the hybrid model that combines digital technology, social capital, and spatial-ecological governance as a framework for adaptive and contextual rural governance. Theoretically, the research findings enrich the literature on sustainable village governance, while practically, this research provides concrete recommendations for policymakers and local stakeholders to strengthen institutional capacity, encourage citizen engagement, and integrate digital innovation into inclusive, resilient, and long-term competitive village development